Morbimortality hospital for pulmonary tuberculosis in Bahia between 2010 2014 - Alana Oliveira Porto; Carla Bianca de Matos Leal; Clessiane de Brito Barbosa; Marcela Andrade Rios (Universidade de Santa Cruz do Sul, 2017)
Background and Objectives:Tuberculosis is anancient disease, but it is still considered a serious public health problem. It is estimated that one third of the world's population is infected with the bacillus, and of these 9.27 million becomeill and 2 million die each year. Thus the present studyaimed to describe the cases of hospitalizations for pulmonary tuberculosis in thest ate of Bahia in the period 2010 to 2014. Methods: This is an epidemiological study of descriptive and cross-sectional conducted based on hospital morbidity and mortality data for pulmonary tuberculosis Bahia, from 2010 to 2014. data were obtained from the Hospital Information System (SIH), electronically available and consolidated in the Department of Informatics of the Unified Health System (DATASUS). Results: Between the years studied were registered in SIH / SUS 5,488 cases of hospitalization for pulmonary tuberculosis in thest ate of Bahia, corresponding to 0.16% of cases of general hospital in that period. Pulmonary tuberculosis is the leading cause of hospitalization as representing 90.6% (n = 5,488) and most hospitalization sand deaths prevailed in the male population aged between 30-59 years and color / race ignored. Conclusion:This study showed that the profile of hospitalization sand deaths due to pulmonary tuberculosis in Bahia in the lastten years, follows a pattern during the study period and remain high, but the costs arising from these hospitalizations were quietly possibly minimized as a result of plans healthaimed at prevention, diagnosis and treatment of disease.